Titanium (IV) oxide-activated nanocarbon from pine wood sawdust and its biocomposites - Md Rezaur, Rahman; Muhammad Khusairy, Bakri; Al-Khalid, Hj Othman; Durul, Huda; Md. Shahid Uz, Zaman; Jamal, Uddin; Mohammed Mahbubu, Matin; Kuok, King Kuok (Elsevier Science, Ltd., 2024)
This chapter will provide information about nanocarbon materials such as nanotubes, graphene, fullerene, and nanodiamond. Pine sawdust will be used as the feedstock to create nanocarbon as it is readily available. Pyrolysis will be used as the process of nanocarbon synthesis. TiO2 grafted nanocarbon biocomposites are manufactured using solvent casting due to its straightforward stages and lack of additional equipment requirements. Scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FTIR), energy-dispersive X-ray spectroscopy (EDS), and other techniques are used to analyze the composite’s morphology and to characterize the TiO2 grafted nanocarbon biocomposite. Finally, research is also done on the uses of nanocarbon and composite.